Language Dominance and Sociolinguistic Experience Are Related to Language Control and Domain-General Monitoring Control: An Investigation in Bilinguals Who Live in a Minority/Majority Sociolinguistic Setting - Wu, Ruilin; Struys, Esli (Frontiers in Psychology, 2021)
Bilingual language control in production tasks with language switches is supposed to be linked to domain-general cognitive control. In the present study, we investigated the role of language dominance, measured on a continuous scale, in the relationship between measures of language control elicited through language switching in a picture naming task and non-linguistic cognitive control induced by stimulus-response interference in a Simon task. In our sample of bilinguals who speak both a minority and majority language (language pair of Uyghur-Chinese), the results showed that as bilinguals were more L2-dominant, a pattern of reversed asymmetry switch costs in language control, i.e., larger L2 than L1 switch costs, was observed. Furthermore, the findings showed that recent exposure to the L1 minority language was associated with the change in language switch costs in terms of both response latencies and accuracy rates. This suggests a role for sociolinguistic context in bilingual language control. Concerning cross-domain generality, globally sustained language control was found to be correlated with domain-general monitoring control in response latencies for all bilingual participants. It lends support to the idea that bilinguals tap into monitoring control in the context of language switching. Additionally, the cross-domain overlap was found between two non-equivalent measures (global language control vs. cognitive inhibitory control) in response latencies, specifically for L1-dominant bilinguals. This suggests that language dominance may have an impact on cross-domain generality in language-switching processes.